Hemigrammus tocantinsi: a new species from the upper rio Tocantins basin, Central Brazil (Characiformes: Characidae) - Carvalho,Fernando R (2010)
Hemigrammus tocantinsi is described from the upper rio Tocantins basin, Chapada dos Veadeiros, Goiás State, Central Brazil. The new species differs from its congeners by the presence of 15-17 branched anal-fin rays, longitudinal stripe relatively narrow anteriorly and wider posteriorly, and one or two maxillary teeth. Sexual dimorphism of the new species is characterized by differences among the color in life, adipose-fin origin, body measurements, in addition to presence of bony hooks in the anal and pelvic fins of males.